Task-constrained self-initiated attention shifts are indexed by frontal-midline theta ramping - Hou, Dengzhe; Sun, Sai; Hatori, Yasuhiro; Tseng, Chia-huei; Shioiri, Satoshi (Frontiers in Human Neuroscience, 2025)
In everyday vision, we often shift attention internally without external cues. These self-initiated attention shifts are fundamental to voluntary behavior but are poorly understood because most studies use cue-based paradigms that predetermine when and where to shift attention. To address this gap, we designed a multi-sequential-choice rapid serial visual presentation (RSVP) paradigm with identical visual inputs to dissociate internal and external determinants of attention across three voluntary shift types: task-constrained self-initiated, externally instructed, and unconstrained free-viewing. Participants viewed four simultaneous streams of letters and made overt attention shifts among them, while EEG was recorded. We time-locked theta (4–7 Hz) and alpha (8–12 Hz) oscillations to shift onset and found distinct signatures for each condition. Notably, a frontal-midline theta ramping was observed before self-initiated shifts but not before instructed or free-viewing shifts, suggesting a preparatory buildup of cognitive control specific to internally driven shifts. Concurrently, sustained suppression of posterior alpha occurred before self-initiated shifts. In contrast, instructed and free-viewing shifts showed relatively higher posterior alpha. These findings suggest that internally generated, goal-driven shifts engage an anticipatory frontal control mechanism indexed by theta increase and reduce posterior inhibition, whereas externally cued or unguided shifts do not. By isolating these condition-specific neural dynamics under identical external stimuli, our study identifies a unique oscillatory signature, frontal-midline theta ramping, associated with task-constrained self-initiated attention shifts.